2015
DOI: 10.1063/1.4922218
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic magneto-optical spectra of GaMnAs

Abstract: In the spectrum of reflection magnetic circular dichroism (MCD) of Ga1−xMnxAs, the E0 peak energy, which is assigned to the band gap of GaMnAs, is higher than the band gap energy of GaAs. In the past, this blue shift was attributed to the Moss-Burstein effect, in which the Fermi level moves toward lower energy in the valence band as the Mn concentration x increases; however, this picture is inconsistent with the impurity-band conduction picture, which has been verified in recent studies. Here, by measuring ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Generally speaking, these observations are consistent with the previous studies of (Ga,Mn)As ternary alloys where several authors have reported a moderate dependence of the MO properties on the Mn concentration. 11,25,26,30,31,34 It is worth mentioning that the spectral dependence of the magneto-optical Kerr effect obtained using the 40-band k.p model in (Ga,Mn)(As,P) is in much better agreement with experimental results than in ternary (Ga,Mn)As using the 30-band k.p model. 30 We believe that the more accurate description of the MOKE originates from a better description of the bands with our 40-band k.p model in particular, from a good determination of the BS details over a wide range of k-vectors in four directions.…”
Section: Moke Spectrasupporting
confidence: 72%
See 1 more Smart Citation
“…Generally speaking, these observations are consistent with the previous studies of (Ga,Mn)As ternary alloys where several authors have reported a moderate dependence of the MO properties on the Mn concentration. 11,25,26,30,31,34 It is worth mentioning that the spectral dependence of the magneto-optical Kerr effect obtained using the 40-band k.p model in (Ga,Mn)(As,P) is in much better agreement with experimental results than in ternary (Ga,Mn)As using the 30-band k.p model. 30 We believe that the more accurate description of the MOKE originates from a better description of the bands with our 40-band k.p model in particular, from a good determination of the BS details over a wide range of k-vectors in four directions.…”
Section: Moke Spectrasupporting
confidence: 72%
“…6,18,19 Magneto-optical microscopy uses the MOKE to gain insight into the magnetic domains static pattern 7,20,21 and the domain wall dynamics. 22 While the MO effects in (Ga,Mn)As have been extensively investigated, [13][14][15][16][23][24][25][26][27][28][29][30][31][32][33][34] the MO properties of (Ga,Mn) (As,P) thin films, more specifically the interplay between the Mn doping and P substitution, remain to be investigated. Hence, in the present study, we report on the MOKE in the interband transition range for ferromagnetic (Ga,Mn)(As,P) samples with different P and Mn contents.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the optical detection either for magneto-optical imaging or in time-resolved experiments, it is important to determine the wavelength dependence of the MOKE. However, the MOKE is also dependent on the layer thickness, the layer and substrate indices, all the more in weakly absorbing magnetic materials as semiconductors or insulators [21][22][23][24]. It is therefore of prime importance to retrieve the intrinsic magneto-optical parameters, depending only on the bulk material structure.…”
Section: Introductionmentioning
confidence: 99%
“…They were found that the peak position and intensity of MO spectra are very sensitive to the film thickness. Despite the increasing role of ferromagnetic semiconductors over the last two decades and the extensive studies available on their magnetic properties, there are few experimental studies of their magneto-optical properties [23,24]. Sun et al studied the polar Kerr rotation for GaMnAs samples with out-of-plane magnetic easy axis and modeled the dielectric function but did not study the layer thickness dependence of the magnetooptical effects [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation